Petra plants a mango tree (Malaysia : Teachatot publications, 2007)
The story follows a young girl named Petra who dreams of planting a mango tree. Throughout her journey, she learns about the importance of nurturing the environment and the responsibility that comes with planting a tree. As Petra cares for her mango tree, she discovers the value of patience as she waits for it to grow and bear fruit. The narrative beautifully illustrates the connection between nature and personal development, showing how nurturing something can lead to positive outcomes over time. Petra's experiences inspire readers to appreciate nature and consider their role in caring for the environment. Overall, the book serves as an engaging and educational tale, promoting environmental stewardship and the joys of gardening for young audiences.
Keywords: English - fiction; English - fable